2008
DOI: 10.4028/www.scientific.net/msf.591-593.799
|View full text |Cite
|
Sign up to set email alerts
|

Use of Kaolin Processing Waste for the Production of Mullite Bodies

Abstract: Mullite is a versatile material used in traditional and advanced ceramic, due to low thermal expansion, high thermal shock and creep resistance. The production of waste from ore industry is a problem that is increasing nowadays. The kaolin processing industry produces residue rich in Al2O3 and SiO2. These oxides are good precursors to produce mullite. The aim of this work is to use the residue from kaolin industry to produce mullite ceramic bodies. It was studied alumina, clay and residue from kaolin processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…This result is in connection with the ceramic properties of the sample presented in Figures 7-9 concerning the firing behaviour with the vitrification features (see Section 3.5). Then, ceramic bodies with high relative proportion of crystalline mullite and minor of quartz, besides vitreous phase, can be obtained by firing at 1300-1350 • C. In general, these thermal features are in agreement with previous results reported in studies on kaolinitic clays [19,34,39,56,60].…”
Section: Development and Evolution Of Crystalline Phases By Thermal T...supporting
confidence: 89%
See 1 more Smart Citation
“…This result is in connection with the ceramic properties of the sample presented in Figures 7-9 concerning the firing behaviour with the vitrification features (see Section 3.5). Then, ceramic bodies with high relative proportion of crystalline mullite and minor of quartz, besides vitreous phase, can be obtained by firing at 1300-1350 • C. In general, these thermal features are in agreement with previous results reported in studies on kaolinitic clays [19,34,39,56,60].…”
Section: Development and Evolution Of Crystalline Phases By Thermal T...supporting
confidence: 89%
“…Several important industries use this kind of refractories, for instance iron and steel, cement, catalysts, petrochemicals, glass and many other advanced functional applications [20][21][22][23][24][25][26][27][28][29][30][31][32]. Thus, it is very important and a real problem the valorization of mining residues by the production of mullite-based ceramic materials [32][33][34][35][36][37][38][39][40][41]. This investigation is a contribution for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…The kaolin waste generally discarded in the open air causes significant environmental problems; affecting fauna, flora and people's health. Numerous studies have been dedicated to the recycling of kaolin processing waste aimed at the production of bricks, tiles and ceramic coatings [12][13][14][15][16]. However, recycling and reuse of wastes should not only be seen from an environmental point of view but also in terms of economic viability.…”
Section: Introductionmentioning
confidence: 99%
“…Tables 15-17 list the chemical composition of primary kaolin industry waste, processing parameters and technological properties of the ceramic materials developed. Brasileiro et al [133,134] reported the use of the residue from the primary kaolin industry as alternative raw material for the production of mullite ceramics. The kaolin residue is mainly composed of SiO ).…”
Section: Kaolin Processing Wastementioning
confidence: 99%